I was Here - Forman, Gayle (UK Simon & Schuster, 2015)
When her charismatic best friend, Meg, drinks a bottle of industrial-strength drain cleaner alone in a motel room, a piece of Cody dies, too. Meg was everything to her. How could Cody not know? Determined to find out what really happened, Cody begins a dangerous search to the shadowy fringes of Meg's life where she discovers some unsettling truths about friendship, secrets, forgiveness, and love."-
Keywords: Washington (State) -- Suicide -- Best friends